2020
DOI: 10.1186/s13256-019-2324-0
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal polyp associated with reflux disease: a case report

Abstract: Background: Among the most common benign laryngeal lesions are vocal nodules and polyps. Their etiology is related to vocal abuse. Gastroesophageal reflux disease is a common condition presenting with a broad spectrum of symptoms, among which are extraesophageal manifestations such as laryngeal polyps. Case presentation: A 24-year-old Middle Eastern woman presented to the author's institution with dysphonia and dyspepsia. She underwent endoscopy and was diagnosed with severe reflux disease. In addition, laryng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Masses such as nodules, polyps, granulomas, or tumors near the vocal cord can induce various clinical symptoms such as hoarseness, breathiness, abnormal voice, pain in the ear or neck, and even laryngeal cancer [ 1 ]. Several recent studies have reported the clinical effects of laryngeal masses, such as airway obstruction, tracheostomy, and reflux diseases [ 2 5 ]. When an individual visits a hospital because of a voice disorder or pain, an otolaryngologist first examines their throat using a laryngoscope to check for any structural abnormalities or color changes on or near the vocal cord and larynx.…”
Section: Introductionmentioning
confidence: 99%
“…Masses such as nodules, polyps, granulomas, or tumors near the vocal cord can induce various clinical symptoms such as hoarseness, breathiness, abnormal voice, pain in the ear or neck, and even laryngeal cancer [ 1 ]. Several recent studies have reported the clinical effects of laryngeal masses, such as airway obstruction, tracheostomy, and reflux diseases [ 2 5 ]. When an individual visits a hospital because of a voice disorder or pain, an otolaryngologist first examines their throat using a laryngoscope to check for any structural abnormalities or color changes on or near the vocal cord and larynx.…”
Section: Introductionmentioning
confidence: 99%